The northern world of the Anglo-Saxon mappa mundi. (December 2018) - Appleton, Helen
Abstract: The Anglo-Saxon mappa mundi, sometimes known as the Cotton map or Cottoniana, is found on folio 56v of London, British Library, Cotton Tiberius B. v, which dates from the first half of the eleventh century. This unique survivor from the period presents a detailed image of the inhabited world, centred on the Mediterranean. The map's distinctive cartography, with its emphasis on islands, seas and urban spaces, reflects an Insular, West Saxon geographic imagination. As Evelyn Edson has observed, the mappa mundi appears to be copy of an earlier, larger map. This article argues that the mappa mundi 's focus on urban space, translatio imperii and Scandinavia is reminiscent of the Old English Orosius, and that it originates from a similar milieu. The mappa mundi 's northern perspective, together with its obvious dependence on and emulation of Carolingian cartography, suggest that its lost exemplar originated in the assertive England of the earlier tenth century.